Durability of Clay Roofing Tiles under Salt Mist Atmosphere - Cruz, C. (2008)
Clay tiles are largely used in traditional construction in Portugal. In coastal zones some cases of accelerated decay have been affecting the roofing tiles durability, apparently due to the exposition to a salt mist atmosphere. To evaluate the performance of the clay roofing tiles subjected to a sea environment, an experimental study is being carried out based on artificial accelerated weathering tests. The study includes the roofing tiles characterization, the development of accelerated weathering tests, the evaluation of the weathering effect through observation and physical and chemical tests and also the comparison with roofing tiles that suffered natural weathering in coastal zones of Portugal. The study aims at reproducing the pathology mechanisms observed in real conditions, and identifying the parameters - of both composition and manufacture - having a higher contribution to the decay of roofing tiles to provide industry with relevant data to improve the manufacturing process. This paper presents tests performed on several kinds of tiles and the results obtained regarding soluble salt effects in the specimens’ microstructure. Mercury Intrusion Porosimetry (MIP) was used to assess differences in the porous structure. Soluble salt content profiles after weathering were also performed, aiming to determine the depth of salt crystallization. Accelerated weathering tests can cause different levels of alteration and degradation to ceramic roofing tiles. Hydrophobic tiles may resist longer to salty mist but they can suffer high damage if there is some penetration of salty solution. Tiles present rather diverse porosimetric structures. The concentration of salt crystallization on the outer layers may induce the destruction of thin superficial layers.